2016
DOI: 10.1002/bjs.10137
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score analysis of outcomes following laparoscopic or open liver resection for hepatocellular carcinoma

Abstract: In comparison with the open approach, laparoscopic minor liver resections for HCC improved short-term outcomes, with similar survival results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 30 publications
6
81
1
2
Order By: Relevance
“…LLR also resulted in significantly less bleeding, shorter hospital stays, and fewer complications, with no difference in survival rates. Similar results were reported by Sposito et al (11).…”
supporting
confidence: 92%
“…LLR also resulted in significantly less bleeding, shorter hospital stays, and fewer complications, with no difference in survival rates. Similar results were reported by Sposito et al (11).…”
supporting
confidence: 92%
“…described the utility of LLR for HCC. A later systematic review and meta‐analysis of LLR and open liver resection (OLR) showed no significant difference in surgical curability, but LLR was associated with less invasive than OLR 80, 81, 82. These reports are considered the main evidence supporting the utility of LLR in the setting of HCC, because it is unrealistic to conduct a randomized controlled trial comparing the outcomes of OLR and LLR.…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…Dies spiegelt zum einen die starke Verbreitung der minimalinvasiven Leberchirurgie in asiatischen Län-dern, mit einem hohen Anteil an Patienten mit lebereigenen Tumoren wider, zum anderen erscheint die Laparoskopie gerade bei diesen Patienten Vorteile zu versprechen [28,32]. Das unstrittig geringere Zugangstrauma in der laparoskopischen Chirurgie mit daraus resultierendem geringerem Schmerzmittelbedarf, früherer Mobilisation und kürzeren Liegezeiten reduziert das Komplikationsrisiko bei Patienten mit Leberzirrhose erheblich [14,33].AucheingeringererBlutverlust, der reduzierte Bedarf an Flüssig-keitsgaben, frühere Darmtätigkeit und die Möglichkeit wiederholter Resektionen mit nur geringer Verwachsungsbildung tragen zum besseren Gesamtergebnis der laparoskopischen Leberchirurgie bei Patienten mit HCC und Leberzirrhose bei [28,32]. Daher sollte gerade bei dieser Patientengruppe die laparokopische Resektion der offenen Resektion vorgezogen werden.…”
Section: Hepatozelluläres Karzinomunclassified